﻿Hepatoprotective activity of QBD-based optimized N-acetyl cysteine solid lipid nanoparticles against CCL4-induced liver injury in mice - Bhavana Madupoju; Subhakar Raju Rapaka; Narender Malothu; Prasanna Kumar Desu; Ankarao Areti (Pensoft Publishers, 2023)
Purpose: In the present study, N-acetyl cysteine (NAC)-Solid Lipid Nanoparticles (SLNs) were developed employing the Quality by Design (QBD) approach for the application of hepatoprotective activity. Methods: Using Box-Behnken Design (BBD) three independent variables (Soya lecithin, polysorbate content, and homogenization speed) and four dependent variables (% entrapment efficiency (EE), % drug release (DR), zeta potential (ZP), and particle size (PS)) were chosen for the study. The formulations were prepared by the hot homogenization method and characterized with SEM, FTIR, DSC, and XRD and evaluated their % EE, % DR, PS, and ZP. Developed SLNs were tested for their hepatoprotective activity by an in vivo mice model and compared the effectiveness with free NAC and Silymarin. Results: The optimized NAC-SLNs were found optimum with spherical and intact chemical structure (88.95% EE, 97.15% DR, -43.01 mv ZP, < 200 nm of PS) exhibiting Higuchi model of drug release. In terms of MDA levels, NAC-SLNs had a strong protective impact MDA level (23.09±0.01-21.84±0.01 u mole/mg protein) and were efficient in increasing GPx (16.89±0.01-20.71±0.02 unit/mg protein), GSH (18.94±0.57-24.21±1.00 unit/mg protein), which were reduced in the CCl4-intoxicated group. NAC-SLNs were more effective than NAC at inhibiting the liver enzymes SGOT (150.01±1.5-132.01±0.6 mg/dL), SGPT (100.73±1.1-91.98±2.8 mg/dL), ALP (147.07±0.8-124.79±0.5 mg/dL), and LDH (290.37±3.04-228.25±2.03U/L). Conclusion: The study concludes that NAC-SLNs therapy was not only substantially more effective than NAC, but it also had effects equivalent to a well-known hepatoprotective and antioxidant drug Silymarin.